An Introduction to the Biology of Vision - McIlwain, James T
This textbook is intended for use in a course for undergraduate students in biology, neuroscience, or psychology who have had an introductory course on the structure and function of the nervous system. Augmented by original research reports, it could be used as an ancillary text for beginning graduate students in neuroscience, psychology, and cognitive science. Its primary purpose is to provide a working vocabulary and to acquaint students with the major themes in research on the biology of vision